Hrr25 kinase promotes selective autophagy by phosphorylating the cargo receptor Atg19 - Pfaffenwimmer, Thaddaeus (BlackWell Publishing Ltd, 2014)
Autophagy is the major pathway for the delivery of cytoplasmic material to the vacuole or lysosome. Selective autophagy is mediated by cargo receptors, which link the cargo to the scaffold protein Atg11 and to Atg8 family proteins on the forming autophagosomal membrane. We show that the essential kinase Hrr25 activates the cargo receptor Atg19 by phosphorylation, which is required to link cargo to the Atg11 scaffold, allowing selective autophagy to proceed. We also find that the Atg34 cargo receptor is regulated in a similar manner, suggesting a conserved mechanism.